An adaptive model for software code quality assessment in refactoring tasks based on fuzzy logic - Liubarskyi, Sergii; Yanko, Alina; Zdorenko, Yurii; Khudayarov, Bakhtiyar (Національний технічний університет "Харківський політехнічний інститут", 2026)
The scientific novelty of the research lies in the development of a hybrid adaptive model for software code quality assessment. Unlike existing models, this one is based on fuzzy logic and an ANFIS, which combines expert knowledge with automated training on real data to enhance the objectivity and efficiency of the refactoring process. The proposed ANFIS architecture with trapezoidal membership functions is used to process eight key code smell metrics (WMC, DIT, RFC, LCOM, NOA, NOC, CBO, FANOUT) within the context of Takagi-Sugeno fuzzy inference. This provides a flexible, interpretable, and adaptive assessment of code quality with the ability to automatically tune model parameters based on gradient learning, which significantly increases the accuracy of code quality determination and the model's suitability for various technology stacks and projects. The practical significance of the research lies in the direct implementability and integration of the developed hybrid adaptive model for software code quality assessment into existing static analysis tools and DevOps processes, specifically as plugins for Continuous Integration/Continuous Delivery (CI/CD) systems. This will enable automated, objective, and adaptive monitoring of code quality in real time. In addition, the model has significant potential for extension to various programming languages and technology stacks by analyzing large datasets from open-source repositories, which will enhance its universality and accuracy. A promising direction for future work is to improve the ANFIS architecture by incorporating deep learning methods, which would allow for the automatic detection of new code smells and their interdependencies. The development of interpretable mechanisms to explain the model's decisions will increase developer trust in the system and promote its widespread adoption in both industrial software development and educational processes in software engineering and cybersecurity.

За результатами проведеного дослідження розроблено гібридну адаптивну модель оцінки якості програмного коду на основі нечіткої логіки та адаптивної нейро-нечіткої системи виведення ANFIS, що дозволяє автоматизовано, об’єктивно та гнучко оцінювати якість програмного коду в задачах рефакторингу. Модель використовує вісім ключових code smells-метрик (WMC, DIT, RFC, LCOM, NOA, NOC, CBO, FANOUT). Їх нормалізація та обробка здійснюється за допомогою нечіткої логіки на основі алгоритму Такагі-Сугено. Це забезпечує врахування невизначеності та суб’єктивності експертних оцінок. Архітектура ANFIS дозволяє моделі навчатися на реальних даних з подальшим автоматичним налаштуванням параметрів функцій приналежності та вагових коефіцієнтів правил. Саме це надає змогу адаптуватися до різних технологічних стеків та проєктів. Використання трапецієподібних функцій приналежності підвищує точність моделювання критичних зон code smells, а гібридний алгоритм навчання на основі градієнтного спуску забезпечує високу точність визначення якості коду, що в підсумку сприяє підвищенню ефективності, підтримуваності, розширюваності та безпеки програмного забезпечення.
Адаптивна модель оцінки якості програмного коду в задачах рефакторингу на основі fuzzy-логіки
Keywords: refactoring; code smells; fuzzy logic; ANFIS; software code quality; software cybersecurity; artificial intelligence; рефакторинг; code smells; нечітка логіка; якість програмного коду; кібербезпека програмного забезпечення; штучний інтелект